Cyanotoxin Monitoring and Detection Using Passive Sampling Application (2024)
ABSTRACT: Cyanobacterial blooms in water have been extensively studied as they produce bioactive and toxic metabolites, commonly known as cyanotoxins. Additionally, the presence of cyanobacteria and, consequently, the production of cyanotoxins, have increased in extent and frequency worldwide. Therefore, the risk associated with the presence of these microorganisms and their toxins has become a matter of great concern. On the other hand, conventional processes for water treatment are inefcient for their elimination and/or degradation, so their presence in water persists at trace and ultra-trace concentrations. In this regard, it is important to develop alternatives to monitor cyanotoxins and allow their detection at low levels in water supply and purifcation systems, in order to ensure water of good quality for human consumption. In this work, diferent methodologies, implemented both at laboratory scale and in situ in aqueous bodies, are described. Among these methodologies, traditional and passive techniques are highlighted. Appropriate analytical and sample preparation methods used in the detection and quantifcation of cyanotoxins are also addressed. It was found that the use of passive samplers is a convenient and a costefective method of identifying the presence of these toxins in water at concentrations in the order of μg/L and ng/L. Moreover, studying the by-products generated from the degradation of natural toxins in aquatic environments and evaluating their possible adverse efects is crucial in terms of the management and control of cyanobacteria and cyanotoxin pollution in water.